Marburg virus regulates the IRE1/XBP1-dependent unfolded protein response to ensure efficient viral replication - Cornelius Rohde; Stephan Becker; Verena Krähling (Emerging Microbes and Infections)
Viruses regulate cellular signalling pathways to ensure optimal viral replication. During Marburg virus (MARV) infection, large quantities of the viral glycoprotein GP are produced in the ER; this may result in the activation of the unfolded protein response (UPR). The most conserved pathway to trigger UPR is initiated by IRE1. Activation of IRE1 results in auto-phosphorylation, splicing of the XBP1 mRNA and translation of the XBP1s protein. XBP1s binds cis-acting UPR elements (UPRE) which leads to the enhanced expression of genes which should restore ER homeostasis. XBP1u protein is translated, if IRE1 is not activated. Here we show that ectopic expression of MARV GP activated the IRE1-XBP1 axis of UPR as monitored by UPRE luciferase assays. However, while at 24 h of infection with MARV IRE1 was phosphorylated, expression of XBP1s was only slightly enhanced and UPRE activity was not detected. The IRE1-XBP1 axis was not active at 48 h p.i. Co-expression studies of MARV proteins demonstrated that the MARV protein VP30 suppressed UPRE activation. Co-immunoprecipitation analyses revealed an RNA-dependent interaction of VP30 with XBP1u. Knock-out of IRE1 supported MARV infection at late time points. Taken together, these results suggest that efficient MARV propagation requires specific regulation of IRE1 activity.